Effect of Tai Chi on psychological disorder in college students: A protocol of systematic review and meta-analysis - Jiang, Li-Li (Medicine (Baltimore), 2020)
BACKGROUND: This study will explore the effect of Tai Chi on psychological disorder (PD) in college students (CS). METHODS: A comprehensive literature search of relevant randomized controlled trials will be carried out in electronic databases from inception to the February 29, 2020: PUBMED, EMBASE, Cochrane Library, Web of Science, Chinese Biomedical Literature Database, and China National Knowledge Infrastructure. There are not limitations related to the language and publication time. Study quality will be assessed by Cochrane risk of bias tool, and evidence quality will be appraised by the grading of recommendations assessment, development, and evaluation approach. RevMan 5.3 software will be exploited to perform statistical analysis. RESULTS: The protocol of this proposed study will investigate the effect of Tai Chi on PD in CS. CONCLUSION: The findings of this study will provide helpful evidence for clinical practice, and health related policy maker to develop a better intervention plan for PD in CS. STUDY REGISTRATION NUMBER: INPLASY202040140.